Parametric analysis of recast layer formation in wire-cut EDM of HSLA steel. Issue 1 (October 2016) - Azam, Muhammad; Jahanzaib, Mirza; Abbasi, Junaid; Abbas, Musharaf; Wasim, Ahmad; Hussain, Salman
Abstract This paper presents an experimental investigation to determine the main wire electrical discharge machining (WEDM) process parameters which contribute to recast layer formation in high-strength low-alloy (HSLA) steel. Influence of process parameters, namely, pulse-on time, pulse ratio, power (discharge current), pulse (spark gap), and wire speed, has been explored systematically on hardened HSLA steel by varying machining conditions using factorial design of experiments. Analysis of variance was performed and pulse-on time and wire speed were found to be significant parameters affecting recast layer. Topographical images indicated surface irregularities like craters, globules, and micro-voids which affect the surface morphology of machined surface. Micrographs of SEM revealed existence of three distinguishable surface layers including recast layer (amorphous and columnar structure), heat-affected zone, and base material. EDS analysis was performed, and it was found that recast layer is free of alloying effects from electrode (molybdenum wire); however, surface layer is oxidized.